GROUNDWATER QUALITY ASSESSMENT IN THE RIVER ATBARA ALLUVIAL SEDIMENTS, EASTERN SUDAN - Nayl, Khalid; Elkrail, Adill; Elsheikh, Abdalla; Hago, Hago Ali (Malaysian Journal of Science, 2024)
According to the standard rates for water testing, 45 wells were sampled and analyzed to evaluate and assess the groundwater chemistry, classify the hydrochemical facies, and identify the sources of salinity in the study area. The main constituents determined included Sodium, Potassium, Chloride, Sulfate, Magnesium, Calcium, Nitrate, and Bicarbonate. Electrical conductivity, Total Dissolved Solids, Total and Excess Alkalinity, and pH were measured on-site during field trips. Using Piper’s diagram, chemical information was utilized to identify the groundwater’s chemical facies. Despite most chemical concentrations being within the Sudanese Standards and Metrology Organization (SSMO) and World Health Organization (WHO) standard limits, salinity hazards were observed in the middle part of the study area, such as in Shaoat Sherg, Almugatah Shreg, and Umm Oud villages, attributed to the concentration of sodium and chloride in basaltic rocks. The dissolved solids in the study area ranged between 200 to 800 mg/L. The values of calcium ranged between 6.4 to 90 mg/L. The magnesium ion concentration ranged between 4.8 and 90 mg/L. The sodium concentration ranged between 7 and 420 mg/L. The concentration of chloride ranged between 6 and 1098 mg/L. Potassium ranged between 1.2 and 46 mg/L. The concentration of bicarbonate ranged between 78 and 793 mg/L. The sulfate concentration ranged between 0.5 and 508 mg/L. The nitrate (NO₃⁻) concentration was found to be very small. Based on Piper’s diagram, the samples resulted in 60% being mixed groundwater type and 40% being Na-HCO₃, Na-Cl, and Ca-Mg-HCO₃ groundwater types. Most samples were deemed good for human and agricultural use. Only nine were found to be above the recommended values, with reference to SSMO (2002) and WHO (2008) standards.